2020
DOI: 10.4103/ijp.ijp_998_20
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of effectiveness and safety of favipiravir in the management of novel coronavirus (COVID-19) patients

Abstract: Multiple options are being tried for the management of 2019-nCoV infection since its pandemic started. Favipiravir (FPV) is one of drugs, which is also being tried for the management of 2019-nCoV infection. The present study aimed to evaluate the efficacy and safety of FPV in published literature. Comparative randomized or nonrandomized controlled clinical trials comparing FPV to the standard of care (SOC)/control or other antiviral agent/combinations were included. A total of 12 databases were searched and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Presently used therapeutic agents for the management of COVID-19 include steroid therapy [ 8 ]; remdesivir [ 9 ]; chloroquine; hydroxychloroquine [ 10 - 12 ]; favipiravir [ 13 ]; ivermectin [ 14 ]; convalescent plasma therapy (CPT) [ 15 ]; and adjunctive agents including zinc, vitamin D [ 16 ], folic acid [ 17 ], and anticoagulants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Presently used therapeutic agents for the management of COVID-19 include steroid therapy [ 8 ]; remdesivir [ 9 ]; chloroquine; hydroxychloroquine [ 10 - 12 ]; favipiravir [ 13 ]; ivermectin [ 14 ]; convalescent plasma therapy (CPT) [ 15 ]; and adjunctive agents including zinc, vitamin D [ 16 ], folic acid [ 17 ], and anticoagulants [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported no effect of favipiravir on the need for ICU transfer compared to controls [ 60 , 63 ]. Nausea, vomiting, diarrhea, and elevated uric acid and liver transaminases were the most commonly reported adverse events of favipiravir [ 59 , [61] , [62] , [63] , [64] , [65] ].…”
Section: Resultsmentioning
confidence: 99%
“…Coronavirus disease caused unprecedented challenges to the healthcare 14 . The result of Pairwise meta-analysis shown that lopinavir-ritonavir (0.8319) is the best intervention for treating COVID-19 patients followed by standard care (0.8319), placebo (0.4794), remdesivir (0.2723) and other antivirals (0.0234).…”
Section: Discussionmentioning
confidence: 99%